Regulation of the Hypoxia-Inducible Factor (HIF) by Pro-Inflammatory Cytokines - Mykyta I. Malkov (Cells, 2021)
Hypoxia and inflammation are frequently co-incidental features of the tissue microenvironment in a wide range of inflammatory diseases. While the impact of hypoxia on inflammatory pathways in immune cells has been well characterized, less is known about how inflammatory stimuli such as cytokines impact upon the canonical hypoxia-inducible factor (HIF) pathway, the master regulator of the cellular response to hypoxia. In this review, we discuss what is known about the impact of two major pro-inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), on the regulation of HIF-dependent signaling at sites of inflammation. We report extensive evidence for these cytokines directly impacting upon HIF signaling through the regulation of HIF at transcriptional and post-translational levels. We conclude that multi-level crosstalk between inflammatory and hypoxic signaling pathways plays an important role in shaping the nature and degree of inflammation occurring at hypoxic sites.